A Contemporary History of Exclusion The Roma Issue in Hungary from 1945 to 2015 (Central European University Press, 2016)
The volume presents the changing situation of the Roma in the second half of the 20th century and examines the politics of the Hungarian state regarding minorities by analyzing legal regulations, policy documents, archival sources and sociological surveys. In the first phase analyzed (1945-61), the authors show the efforts of forced assimilation by the communist state. The second phase (1961-89) began with the party resolution denying nationality status to the Roma. Gypsy culture was equivalent with culture of poverty that must be eliminated. Forced assimilation through labor activities continued. The Roma adapted to new conditions and yet kept their distinct identity. From the 1970s, Roma intellectuals began an emancipatory movement, and its legacy is felt until this day. Although the third phase (1989-2010) brought about freedoms and rights for the Roma, with large sums spent on various Roma-related programs, the situation on the ground nevertheless did not improve. Segregation and marginalization continues, and it is rampant. The authors powerfully conclude: while Roma became part of the political community, they are still not part of the national one. Subjects: Romanies-Hungary. Romanies-Hungary-Social conditions. Marginality, Social-Hungary. Romanies-Legal status, laws, etc.-Hungary. Minorities-Government policy-Hungary. Hungary-Ethnic relations. Hungary-Social policy.